Studying Menstruators in IISER Mohali - Nitika (IISER Mohali, 2023)
I chose to study menstruators at IISER Mohali. I used qualitative and quantitative data to analyze various aspects of menstruation, like health and hygiene and the menstrual experiences of these menstruators. My study aimed to understand how menstruators in a residential science institute of national importance perceive menstruation and if menstruation and science impact one another. Doing so helped me find problems these menstruators encounter in their everyday lives and how menstruation, which is very visible to them, is invisible to the other stakeholders like the management of IISER-M. Chapters three to seven of my thesis are based on an analysis of the data. The third chapter overviews menstrual experiences at menarche to understand how the first encounter with menstruation shapes its perception. The fourth chapter explores the difference in menstrual experiences at home, school, and IISER-M. The fifth chapter discusses the stakeholders of menstruation in IISER-M. The sixth chapter talks briefly about the impact of COVID-19 on the lives of these menstruators. The seventh chapter analyzes the interaction of science and menstruation in the everyday lives of these menstruators
Embargo Period
Keywords: Social science